Environmental Law Updates for Combating Urban Air Pollution fromTransportation Emissions Based on Green Constitution Principles - Andhika Laksamana Putra; Hidayati Hidayati (Pelopor Publikasi Akademika, 2026)
This study aims to analyze and reconstruct the law governing the control of urban air pollution from transportation emissions in Indonesia, based on Green Constitution principles. The main problem lies in the weakness of normative regulations and the low effectiveness of law enforcement, despite the constitutional guarantee of the right to a good and healthy environment in Article 28H paragraph (1) and the principle of sustainable development in Article 33 paragraph (4) of the 1945 Constitution of the Republic of Indonesia. This study uses a normative juridical method with a legislative and conceptual approach, analyzing Law Number 32 of 2009 concerning Environmental Protection and Management and its amendments in Law Number 6 of 2023, as well as regulations related to motor vehicle emissions. The results of the study indicate a gap between legal norms and their implementation, characterized by regulatory fragmentation, weak sanctions, and low public compliance with emission tests. Therefore, integrative and transformational legal reform is needed by strengthening state and corporate responsibility, reforming the sanctions system, implementing environmental economic instruments, and utilizing technology for emissions monitoring. This reform is expected to achieve effective and ecologically just environmental protection in accordance with the principles of the Green Constitution.